2020
DOI: 10.1038/s41598-020-69302-6
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/PbS quantum dot hybrid structure for application in near-infrared photodetectors

Abstract: A graphene-PbS quantum dot (QD) composite for application in high-performance near-infrared (NIR) photodetectors (PDs) is proposed in this study. A single-layer graphene flake and oleic acid-capped PbS QD composite is fabricated through the conventional sonication process, in hexane solution. Field emission scanning electron microscopy images of the graphene-PbS QD composite dispersed on a glass substrate confirm that the composite contains both aggregated graphene flakes and single-layer graphene with wrinkle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…[20,22] The Raman spectrum of the graphene-PbS hybrid film was determined and shown in Figure 1b, demonstrating the characteristic peaks of both the monolayer graphene and PbS. [23] The cross-sectional scanning electron microscopy (SEM) image of the hybrid film in Figure 1c shows about 124 nm thickness of the PbS QDs film. Finally, the same graphene strip-Au pad structure was prepared above the QDs film using the same procedure as the bottom one.…”
Section: Resultsmentioning
confidence: 99%
“…[20,22] The Raman spectrum of the graphene-PbS hybrid film was determined and shown in Figure 1b, demonstrating the characteristic peaks of both the monolayer graphene and PbS. [23] The cross-sectional scanning electron microscopy (SEM) image of the hybrid film in Figure 1c shows about 124 nm thickness of the PbS QDs film. Finally, the same graphene strip-Au pad structure was prepared above the QDs film using the same procedure as the bottom one.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene is a good option for room-temperature photodetection purpose because of its several virtues which are greater mobility, less carrier transit time, and good susceptibility to the electrostatic disturbance caused by photogenerated surface carriers. Colloidal QDs synthesized by PbS ( Sun et al, 2012 ; Jeong et al, 2020 ) shown in Figure 7C ( Konstantatos et al, 2012 ) are an example of graphene-sensitized light-absorbing particles. Photon detection at weak incident light intensities, especially at single-photon levels, necessitates a gain mechanism capable of providing numerous electrical carriers for each individual illuminated photon.…”
Section: Overview Of 2d Materials-based Photodetectorsmentioning
confidence: 99%
“…Combining these two promising substances can enhance the photoresponsivity and shorten the response time of the photodetector devices. [ 15–17 ] Perovskite quantum dots (P‐QDs) light‐emitting diode (QLEDs) exhibit luminescent efficiency comparable to the organic light emitting diodes (OLEDs), narrow emission bandwidth, and color‐tunable wavelength, making them promising candidates for next‐generation lighting sources and information display devices. [ 18–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…Combining these two promising substances can enhance the photoresponsivity and shorten the response time of the photodetector devices. [15][16][17] Perovskite quantum dots (P-QDs) light-emitting diode (QLEDs) exhibit luminescent efficiency comparable to the organic light emitting diodes (OLEDs), narrow emission bandwidth, and color-tunable wavelength, making them promising candidates for next-generation lighting sources and information display devices. [18][19][20] Herein, we report a near-infrared (NIR) to visible light converter (NVLC), which integrates the inverted perovskite QLEDs with the hybrid PbS QDs/graphene transistors through multiple micro-nano manufacturing processes.…”
mentioning
confidence: 99%